2022
DOI: 10.1038/s41586-022-05605-0
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells direct circadian anti-tumour immune responses

Abstract: The process of cancer immunosurveillance is a mechanism of tumour suppression that can protect the host from cancer development throughout its lifetime1,2. However, it is unknown whether the effectiveness of cancer immunosurveillance fluctuates over a single day. Here we demonstrate that the initial time of day of tumour engraftment dictates the ensuing tumour size across mouse cancer models. Using immunodeficient mice as well as mice lacking lineage-specific circadian functions, we show that dendritic cells (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 26 publications
2
80
0
Order By: Relevance
“…One of the mechanisms behind this effect is considered to be lymphocyte circadian oscillations. Lymphocyte and dendritic cell homing to lymph nodes occurs in a circadian manner that peaks at the active phase, with cells leaving the tissue during the rest phase [ 15 17 ]. Tumor tissue consists not only of cancer cells, but also numerous non-cancer cells, such as fibroblasts, epithelial cells, lymphocytes, macrophages, and myeloid-derived suppressor cells.…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms behind this effect is considered to be lymphocyte circadian oscillations. Lymphocyte and dendritic cell homing to lymph nodes occurs in a circadian manner that peaks at the active phase, with cells leaving the tissue during the rest phase [ 15 17 ]. Tumor tissue consists not only of cancer cells, but also numerous non-cancer cells, such as fibroblasts, epithelial cells, lymphocytes, macrophages, and myeloid-derived suppressor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages and Dendritic Cells (DCs), two major Antigen Presenting Cells (APCs), are pivotal innate immune cells that regulate the anti-tumour immune responses ( 116 , 117 ). It has been shown that NETs activate macrophages and DCs through upregulating important costimulatory molecules (CD80, CD86) at early times (30 min), however, macrophages and DCs undergo apoptosis after prolonged incubation with NETs ( 118 ).…”
Section: Nets In Immune Cellsmentioning
confidence: 99%
“…For example, BMAL1::CLOCK recruits immune-suppressive microglia cells to the TME of glioblastoma (GBM) via transcriptional activation of the OLFML3 gene (38). Circadian expression of the co-stimulatory molecule CD80 in dendritic cells governs a circadian response of tumor antigen-specific CD8+ T cells to melanoma development (39). The CLOCK protein interacts with HIF-1 to activate VEGF expression, facilitating angiogenesis and metastasis in colorectal cancer (40).…”
Section: Circadian Regulation Of Tumor Microenvironmentmentioning
confidence: 99%